Legal Analysis of the Criminal Act of Trading in Protected Animals Based on Law Number 5 of 1990 Concerning Conservation of Natural Resources and Ecosystems - Damayanty, Risa; Mandasari Saragih, Yasmirah (PT. Multidisciplinary Press Indonesia, 2024)
The crime of trading protected animals is prohibited by law in Indonesia. Because it can threaten the existence of various animals that have spread throughout Indonesia. For that reason, Law Number 5 of 1990 concerning Conservation of Natural Resources and Ecosystems has formulated and threatened criminal penalties for various methods and consequences of actions that commit the crime of trading protected animals.